2020
DOI: 10.1177/1533033820904447
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiation Therapy With Simultaneous Integrated Boost in Patients With Spinal Metastases

Abstract: Stereotactic body radiation therapy in patients with spine metastases maximizes local tumor control and preserves neurologic function. A novel approach could be the use of stereotactic body radiation therapy with simultaneous integrated boost delivering modality. The aim of the present study is to report our experience in the treatment of spine metastases using a frameless radiosurgery system delivering stereotactic body radiation therapy–simultaneous integrated boost technique. The primary endpoints were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Some risk for adverse events is peculiar to the stereotactic technique, which is an approach effectively used also in other metastatic or primary sites [41] , [42] , [43] , [44] in order to prevent the characteristic side effects of less conformal types of external beam radiotherapy [45] , [46] ; this therapeutic option allows to use a high radiation dose in a single fraction or short fractionated radiotherapy schedule. Kano et al [47] conducted a retrospective study involving 755 patients who have been submitted to a median single radiosurgery dose of 20 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Some risk for adverse events is peculiar to the stereotactic technique, which is an approach effectively used also in other metastatic or primary sites [41] , [42] , [43] , [44] in order to prevent the characteristic side effects of less conformal types of external beam radiotherapy [45] , [46] ; this therapeutic option allows to use a high radiation dose in a single fraction or short fractionated radiotherapy schedule. Kano et al [47] conducted a retrospective study involving 755 patients who have been submitted to a median single radiosurgery dose of 20 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Such a key point is of fundamental importance not only in the cerebral region but also in other neuroaxis-related sites; for example, any damage to the vertebral column could be life-altering. The risk for vertebral compression fracture is especially feared when treating bone metastases to the vertebral body with high radiation doses [9].…”
mentioning
confidence: 99%
“…In line with previous reports on choroidal metastases, we also found that radiotherapy significantly ameliorates clinical and functional status in patients with orbital metastases ( p = 0.032), favoring nonsurgical lesion shrinkage and relief of mass effect [ 22 , 54 ]. Although some cases of radiation-induced cataracts have been reported in earlier studies [ 55 ], modern image-guided radiotherapy planning allows the delivery of maximal doses to selected targets [ 56 , 57 ], sparing critical orbital structures and preventing the onset of severe adverse events [ 55 , 58 , 59 , 60 ]. Thus, radiotherapy appears to be safe and effective in the treatment of orbital metastases similarly to choroidal metastases, but the severity of radiation-induced complications might differ due to the unfortunate proximity of choroidal metastases to the macula and lens [ 54 , 61 ].…”
Section: Discussionmentioning
confidence: 99%